ROLE OF "ATYPICAL" MICROORGANISMS ON THE FORMATION OF BRONCHIAL ASTHMA IN CHILDREN WITH ACUTE AND RECURRENT OBSTRUCTIVE BRONCHITIS - Zhukova, Olga V; Kononova, Svetlana V; Konyshkina, Tatjana M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was undertaken to determine the link between the presence of atypicalâ€ infections in patients with acute obstructive and recurrent obstructive bronchitis (AOB/ROB) and bronchial asthma (BA) development based on the concept of risk. Methods: The materials for the study were the data records of patients hospitalized with AOB or ROB and whose analysis was performed to identify antibodies to atypicalâ€ microflora (796 patients). The study period was 4 years from 2008 to 2011. In the analyzed period, immunosorbent assay for the detection of antibodies to atypicalâ€ microflora (Chlamydophila pneumoniae, Mycoplasma pneumoniae, Mycoplasma hominis) was performed. The concept of risk identification was based on the determination of the absolute risk, attributable risk (AtR), relative risk, population attributable risk, as well as on the definition of the standard errors for each type of risk and the confidence interval. Results and Conclusion: Methodical aspects of determining the relationship between the presence of atypicalâ€ infections in patients with AOB or ROB and BA development were based on the concept of risk. The analysis showed a direct link between the increase of cases of BA formation against the backdrop of atypicalâ€ infections. Therefore, the performed analysis of atypical pathogens influences on BA occurrence in patients with AOB/ROB which indicates direct dependence increase of BA incidence on atypical infection. In experimental group, Frequency of event is 14.84% in experimental group. Frequency of event is 1.67% in control group. The risk factor increases probability of event by 13.17%, the risk factor increases probability of event by 13.17%. Presence of atypical infection leads to increase of BA incidence by 8.9 times. Number needed to harm (NNH) is 7.59, i.e., in the presence of atypical infection in patients with AOB/ROB, each eighth exposed person develops BA in addition to background level of BA incidence. Keywords: Acute obstructive bronchitis, Recurrent obstructive bronchitis, Bronchial asthma, The concept of risk, Risk factor, The absolute risk, Relative risk, Attributable risk, Population attributable risk, Number needed to harm.